The Undeclared, Declassified: West New Guinea and the 1969 Act of Free Choice - Greg Poulgrain (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2022)
This article deals with the ‘Act of Free Choice’ (AFC/Pepera) whereby Indonesia officially took control of West New Guinea under the auspices of the United Nations (UN). The event itself took place in 1969 as preordained in the terms of the New York Agreement of August 1962 drawn up by US diplomat, Ellsworth Bunker. In both the 1962 Agreement and the 1969 AFC, Adam Malik was the principal Indonesian participant; and in both, according to his 1969 Report, the role of the UN was really no more than a bystander. Yet it was the authority of the UN which ultimately provided approval of Indonesian sovereignty as the outcome of the AFC. How this came about is evident from a close inspection of US declassified telegrams from 1966-1999. Two principal questions arise: the first pertains to the motivation of the various US diplomats involved, such as Bunker, Marshall Green (US Ambassador to Indonesia 1965-69) and Henry Kissinger, who were linked to Rockefeller mining interests focused on gaining access to the world’s largest gold mine in West New Guinea; and the second pertains to the rights of the Papuan people as the inhabitants of the territory in question. In the written words and opinions of the persons who were actually involved in the preparation and execution of the AFC/Pepera, there is often no compunction in disregarding UN principles, and yet there is a willingness, when it suits, to utilize UN authority as the arbiter of international justice.